2018
DOI: 10.1111/1471-0528.15437
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term outcomes in children born after assisted reproductive technology

Abstract: It has been forty years since the first IVF child, Louise Brown, born in 1978 and now more than 7 million children are conceived after assisted reproductive technologies (ART). There has been a tremendous increase in the number of ART cycles and several more advanced treatments have been developed, such as intracytoplasmic sperm injection (ICSI). ICSI revolutionized the treatment of severe male factor infertility after the first ICSI baby born in 1992. This article is protected by copyright. All rights reserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…In 2010, 48.5 million couples worldwide were estimated to be affected by infertility [ 1 ]. The use of in vitro fertilization (IVF) and other assisted reproductive technologies (ART) is expanding rapidly, accounting for more than seven million births worldwide [ 2 ]. The advancement of treatments and changes in protocols have also reshaped the landscape of fertility practice in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, 48.5 million couples worldwide were estimated to be affected by infertility [ 1 ]. The use of in vitro fertilization (IVF) and other assisted reproductive technologies (ART) is expanding rapidly, accounting for more than seven million births worldwide [ 2 ]. The advancement of treatments and changes in protocols have also reshaped the landscape of fertility practice in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the occurrence of autism and cerebral palsy in IVF/ICSI-derived children was found to be increased in some (Stromberg et al 2002, Lehti et al 2013, Sandin et al 2013, Kamowski-Shakibai et al 2015, Schieve et al 2017, Goldsmith et al 2018 but not all studies (Kallen et al 2010, Reid et al 2010. Both autism (Fountain et al 2015) and cerebral palsy (Goldsmith et al 2018) have been strongly associated with multiple births in ART pregnancies highlighting the need to reduce multiple pregnancies in women undergoing ART (Pinborg 2019).…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%
“…Also, a critical step in elucidating the long-term effects of ART in human populations is the development of databases for ART surveillance (i.e. health monitoring of ART-derived offspring), something that has been implemented in just a few countries (Pinborg 2019). The first ART-derived baby turned 40 years just recently, hence the long-term repercussions (or lack of) of ART for healthy ageing are far from being elucidated.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%
“…In developed countries, 1-6% of children are currently conceived by ART, mostly IVF and ICSI (Calhaz-Jorge et al, 2015;Goisis et al, 2019;Pinborg et al, 2019). Even though these procedures are generally considered to be safe, there are remaining concerns about their longterm health consequences (Celermajer, 2012;Calhaz-Jorge et al, 2015, Goisis et al, 2019Pinborg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, 1-6% of children are currently conceived by ART, mostly IVF and ICSI (Calhaz-Jorge et al, 2015;Goisis et al, 2019;Pinborg et al, 2019). Even though these procedures are generally considered to be safe, there are remaining concerns about their longterm health consequences (Celermajer, 2012;Calhaz-Jorge et al, 2015, Goisis et al, 2019Pinborg et al, 2019). As recently reviewed, several studies have suggested that individuals conceived by ART might be at risk of developing increased adiposity, glucose intolerance and hypertension, although there is no general agreement on these findings and correction for confounding factors such as maternal hormonal environment following ovarian stimulation, embryo culture conditions, fresh or frozen embryo transfer, single or multiple embryo replacement and parental age and/or infertility (Pinborg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%